Implementation of the Collaborative Principles on Marine Tourism: Lessons from Mud Island, Indonesia - Rahmat Teddy Hariadi; Agus Subianto; Lunariana Lubis (Universitas Pendidikan Ganesha, 2022)
This paper aims to examine marine tourism as an empirical phenomenon. To gain insight into the systemic conditions of the collaboration process, it is observed from the point of view of the principles of the collaboration process from Roberts, Van Wyk & Dhanpat. The authors identify the principles implemented in the collaborative process between the Community, Village-Owned Enterprises, and the Government in a collaborative network towards sustainable marine ecotourism. This analytical descriptive study used case survey methods in the partnership networks. The data is obtained through a qualitative approach, observation, semi-structured interviews, and documentation. The findings reveal that stakeholders involved in the collaboration contribute to realizing a common purpose and providing mutual benefits, but the quality of collaboration is not optimal because it is still informal. Lessons learned from the application of collaboration principles on marine tourism in the Lusi Mud Island, Sidoarjo Regency, Indonesia are: the importance of trust and enabling environmental factors that collaboration to be realized; the importance of the characteristics of community leaders who have a deep concern as leaders, and ensure the participation of local communities in the development and management stages of marine tourism towards marine ecotourism.